Anaesthesiology and intensive careComparison of continuous use of thoracic epidural analgesia and intercostal block for pain management after thoracotomy - Sagiroglu, Gonul; Baysal, Ayse; Kiraz, Osman Gazi; Meydan, Burhan; Taşçı, Ahmet Erdal; Iskender, Ilker (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Aim of the study: We aimed to compare the efficacy of the continuous use of thoracic epidural and intercostal analgesia for post-thoracotomy pain. Material and methods: Sixty patients completed a prospective, randomized, double-blinded study. The patients were randomized to receive thoracic epidural (group 1, n = 30) or intercostal block (group 2, n = 30) for 24 hours. In both groups, 0.25% bupivacaine was infused at a rate of 5 ml/h through an inserted catheter. Visual analog scale at rest (VAS-R) and after coughing (VAS-C) scores were recorded at baseline and at 1, 6 and 24 hours after surgery to evaluate pain. Morphine consumption, complications and side effects were recorded as well. Results: VAS-R and VAS-C scores were similar at baseline; however, 1 st , 6 th and 24 th hour scores of group 1 were significantly lower than the scores of group 2 (for VAS-R; p = 0.017, p = 0.001, p = 0.023, for VAS-C; p = 0.006, p = 0.002, p = 0.032, respectively). 24-hour morphine consumption was lower in group 1 in comparison to group 2 (p = 0.032). In group 1, 5 out of 30 patients (17%) experienced hypotension, compared with none in group 2 (p = 0.02). Conclusions: For post-thoracotomy pain, better control of analgesia is observed with the thoracic epidural technique; however, intercostal block constitutes an alternative method as it is characterized by lower incidence of hypotension.